Solving the innovation mystery : a workplace whodunit - Gladis, Stephen D. (ATD Press, 2016)
"There isn't a CEO on the planet who hasn't considered the importance of innovation. In the face of global competition and the explosion of technology, innovation is today's business imperative. How else does a company remain both productive and adaptive? In Solving the Innovation Mystery: A Workplace Whodunit, leadership authority Steve Gladis deftly solves the innovation equation. He gets at the slower moving truth of how innovation actually happens and shows just why we must resist the hero tale and the mirage that is the eureka moment. Delve into the experimentation, failure, and learning that make innovation possible as you get to the heart of innovation's collaborative nature. Then solve your own innovation equation by understanding how to fuel your company's innovation engine systematically, paving a straight path to commercializing creative business solutions. Solving the Innovation Mystery: A Workplace Whodunit delivers an entertaining tour de force part theory, part story as Gladis tracks private investigator Roland Epps and executive coach Dana Glass to illustrate his innovation thesis that a safe, trusting culture is essential for creativity to thrive and for innovation to take root."--Page [4] of cover.